The Effect of Cooperative Learning Models Ice Breaking Based Tournament Games Teams Type To Motivation and Results Study in Mathematics Subject for 3rd Grade Elementary School in Sapanang Ward, Bungoro District, Pangkep Regency - Fifi Indriani; Sukmawati S; Andi Husniati (Indonesian Journal of Primary Education, 2023)
Quasi experimental design quantitative research was carried out and aims to determine the effect of the Teams Games Tournament (TGT) type cooperative learning model assisted by Ice Breaking on the motivation and learning outcomes of students in class III Elementary School Sapanang Ward , Bungoro District , Pangkep Regency, collecting technical data using tests and questionnaires. A pretest as the initial result before being given treatment and at the end of the meeting given a post-test as a result of giving the treatment. Furthermore, the data obtained was analyzed using the SPSS v.26 application by looking for the results of the normality test, homogeneity test and Independent Sample t-Test to test the hypothesis. The average score obtained by students in the pretest control class was 68.12 and the posttest was 67.92. While the average score obtained by students in the pretest experimental class was 63.14 and the posttest was 80.68. The results of inferential data analysis obtained sig. 0.000. It turns out that the value of sign. 0.000 is smaller than the probability value of 0.05 or in other words the value of 0.05 0.000. Then H0 is rejected and H1 is accepted, meaning that the coefficient of data analysis is significant. So it can be interpreted that, there is an influence of the Teams Games Tournament (TGT) type of cooperative learning model assisted by Ice Breaking on the motivation to learn mathematics in class III elementary school students.